Academic Stress and Primary Dysmenorrhea in Medical Students Tanjungpura University - Idelle Ariqa; Emika Prastyan; Iit Fitrianingrum (Universitas Muhammadiyah Malang, 2025)
Introduction: Academic stress is common among medical students, particularly women who may be hormonally more susceptible. Primary dysmenorrhea—menstrual pain without pelvic pathology—is often intensified by stress and can hinder academic performance. Objective: To examine the relationship between academic stress and primary dysmenorrhea among female medical students at Tanjungpura University. Methods: This analytical observational study used a cross-sectional design involving 123 female medical students selected through proportionate stratified random sampling. Academic stress was measured using the Medical Student Stress Questionnaire (MSSQ), and menstrual pain was assessed with the Numeric Rating Scale (NRS). Data were analyzed using the Spearman correlation test. Result: Most respondents reported severe academic stress (57.7%) and mild dysmenorrhea (44.7%). A moderate positive correlation was found between academic stress and dysmenorrhea severity (r = 0.302; p = 0.0001). Conclusion: A meaningful relationship exists between academic stress and the severity of primary dysmenorrhea in female medical students. The use of MSSQ highlights academic stressors specific to medical training. Targeted stress management strategies may help reduce menstrual pain and improve student well-being.